Development of monoclonal antibody against IgT of a perciform fish, large yellow croaker (Larimichthys crocea) and characterization of IgT+ B cells. (June 2021) - Fu, Qiuling; Wei, Zuyun; Chen, Yuhong; Xie, Jingguang; Zhang, Xiangyang; He, Tianliang; Chen, Xinhua
Abstract: Teleost immunoglobulin T (IgT) is considered to be a primitive immunoglobulin class specialized in mucosal immunity. In the present study, a recombinant protein containing the CH2 region of large yellow croaker ( Larimichthys crocea ) IgT heavy chain was expressed, purified, and used as an immunogen to produce a monoclonal antibody (mAb) against large yellow croaker IgT. Western blotting results indicated that the obtained mouse anti-IgT mAb could specifically recognize a 45 kDa protein in the skin mucus of large yellow croaker, which was identified as the IgT heavy chain by mass spectrometric analysis. Immunofluorescence assay (IFA) analysis further demonstrated that this mouse anti-IgT mAb could recognize membrane-bound IgT (mIgT) molecules on large yellow croaker IgT + leukocytes. This mAb also could be used for sorting of large yellow croaker IgT + B cells by flow cytometry sorting technology. Then, flow cytometric immunofluorescence analysis (FCIA) results showed that the percentages of IgT + B cells in skin, gills, gut, spleen, head kidney and peripheral blood lymphocytes were 27.553% ± 3.312%, 12.588% ± 3.538%, 12.355% ± 3.352%, 13.075 ± 2.258%, 5.552 ± 3.275%, and 2.600 ± 0.521%, respectively, indicating that mucosal tissues (skin, gills, and gut) contained a high ratio of IgT + B cells. Accordingly, the high protein levels of IgT were also detected in these mucosal tissues, suggesting that IgT may play a role in mucosal immunity in large yellow croaker. Taken together, our data demonstrated that the mouse anti-IgT mAb developed in this study could be used for characterizing IgT + B cells and studying the functions of IgT in large yellow croaker. Highlights: A monoclonal antibody (mAb) against large yellow croaker IgT was developed. This mAb recognizes both soluble and membrane-bound large yellow croaker IgT. This mAb can be used for characterizing IgT + B cells of large yellow croaker. High percentages of IgT + B cells and high levels of IgT were observed in mucosal tissues. IgT may play a role in mucosal immunity in large yellow croaker.